Sociologia dei quartieri urbani - Castrignanò, Marco (Sociologia del territorio, 2021)
The pandemic crisis has made increasingly relevant and urgent to reflect on the way our cities are organised, on an intra-urban scale. The book aims to bring to the reader's attention the theme of urban neighbourhoods, approaching it from a sociological point of view. The first two chapters outline the theoretical and analytical framework of the neighbourhood approach, contextualising social capital in a differentiated urban dimension within it and recognising the specificity of places and territories in which collective life is organised. In the central chapters, declined in more applicative terms, the reflection focuses on spatialisation of public housing and social mix in the city of Bologna; on residential practices and strategies in the Scampia district (Naples), from which the dynamics of an informal real estate market of social rents emerge. The book continues with an action-research on neighbourhood effect and equity in the right to health within the urban context of Bologna. The final chapter is dedicated to the sustainable city and the importance of neighbourhoods in facing the global challenge of climate change.